Onboard dynamic image exposure control for the Star–Planet Activity Research CubeSat (SPARCS). Issue 4 (3rd December 2021) - Ramiaramanantsoa, Tahina; Bowman, Judd D; Shkolnik, Evgenya L; Loyd, R O Parke; Ardila, David R; Jewell, April; Barman, Travis; Basset, Christophe; Beasley, Matthew; Cheng, Samuel; Gamaunt, Johnathan; Gorjian, Varoujan; et al.
ABSTRACT: The Star–Planet Activity Research CubeSat ( SPARCS ) is a 6U CubeSat under development to monitor the flaring and chromospheric activity of M dwarfs at near-ultraviolet (NUV) and far-ultraviolet (FUV) wavelengths. The spacecraft hosts two UV-optimized delta-doped charge-coupled devices fed by a 9-cm telescope and a dichroic beam splitter. A dedicated science payload processor performs near-real-time onboard science image processing to dynamically change detector integration times and gains to reduce the occurrence of pixel saturation during strong M dwarf flaring events and provide adequate flare light-curve structure resolution while enabling the detection of low-amplitude rotational modulation. The processor independently controls the NUV and FUV detectors. For each detector, it derives control updates from the most recent completed exposure and applies them to the next exposure. The detection of a flare event in the NUV channel resets the exposure in the FUV channel with new exposure parameters. Implementation testing of the control algorithm using simulated light curves and full-frame images demonstrates a robust response to the quiescent and flaring levels expected for the stars to be monitored by the mission. The SPARCS onboard autonomous exposure control algorithm is adaptable for operation in future point source-targeting space-based and ground-based observatories geared towards the monitoring of extreme transient astrophysics phenomena.